2007
DOI: 10.1063/1.2768317
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic collimation of fast electrons produced by ultraintense laser irradiation by structuring the target composition

Abstract: A scheme for collimating fast electrons in a specially engineered solid target is proposed. Unlike previous approaches, the collimation is achieved by generating an azimuthal magnetic field as opposed to a radial electric field. The target is engineered such that it consists of a fiber surrounded by material of a lower resistivity than that of the fiber. The fast electrons are collimated along the fiber. Hybrid Vlasov-Fokker-Planck simulations supported by analytic calculations show that this concept is viable. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
138
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(139 citation statements)
references
References 35 publications
1
138
0
Order By: Relevance
“…Previously, the self-pinch of fast electron beam due to the first term was expected [5,6]. However, for the case of fast electron beam with large divergence, it does not work well.…”
Section: Resistive Guiding By "Tongari" Cone Tipmentioning
confidence: 99%
“…Previously, the self-pinch of fast electron beam due to the first term was expected [5,6]. However, for the case of fast electron beam with large divergence, it does not work well.…”
Section: Resistive Guiding By "Tongari" Cone Tipmentioning
confidence: 99%
“…Several artificial approaches have been proposed to overcome this issue. Robinson and Sherlock 17 proposed to apply a material having a higher resistivity core and lower resistivity cladding to induce an azimuthal magnetic field at the interface, which has been shown to be very effective for collimating fast electrons in recent experiments. 18,19 A concept of using a generator prepulse to produce a magnetic field that collimates the fast electrons injected into the target by the main pulse has also been proposed by Robinson et al 20 Recently, Sentoku et al 21 demonstrated that the fast electron propagation in metals can be controlled dynamically using ionization-driven resistive magnetic field by tuning the target ionization dynamics both in experiments and numerical particle-in-cell (PIC) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Collisions are included using the Fokker-Planck collisional operators, which account for angular fast electron scattering from background ions and electrons, together with drag generated by the background electrons. The mathematical expressions of the collisional operators are obtained from Davies 13 equations (1) and (2). More details about the physics of hybrid code can be found in the study by Robinson et al 8 A 200 Â 100 Â 100 grid was used with a 0.5 lmc e l ls i z e in each direction.…”
Section: Simulation Set Upmentioning
confidence: 99%
“…The ability of a resistive guide to confine fast electrons depends on the ratio of the fast electron Larmor radius to the generated azimuthal magnetic field width L / . The confinement condition of the fast electrons along the guide is expressed as 2,5 B / L / ! P f e 1 À cos h d ðÞ ;…”
Section: Introductionmentioning
confidence: 99%